2022
DOI: 10.1155/2022/1031211
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Effect of Repeated Exposure to Extremely Low-Frequency Electromagnetic Field (50 Hz) of 1 and 7 mT on Oxidative/Antioxidative Status in Rat’s Brain: The Prediction for the Vulnerability to Diseases

Abstract: Studies reported evidence for opposite effects of extremely low-frequency electromagnetic field (EMF): harmful, including the oxidative stress induction, and beneficial, such as the activation of antioxidant defense. People’s exposure to EMF is often repeated or prolonged, and it is important to consider the cumulative effect of such kind of exposure on the organism. If changes evoked by repeated exposure to EMF are permanent, responsiveness to other stress factors can be modified. The aims of our study were (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…EMFs modulate the efficiency of cell death by altering the expression of calmodulin (CaM) and CaM-dependent proteins [42]. In summary, various in vitro and in vivo experimental studies highlighted here for their scientific quality [31][32][33][34][35][36][37][38][39][40][41][42] agree that the effect of ELF-MF (modulated or unmodulated) at the immune cell level depends on the oxidative status. Non-ionizing radiation in the 35-50 Hz frequency range and intensity of 1 to 7mT modulates antioxidant enzymes, increasing intracellular calcium levels, favouring therapy after cerebral vascular accidents, by modulating apoptosis caused by cytotoxic agents.…”
Section: Emf-induced Redox Stress May Modulate Apoptosis And/ or Necr...mentioning
confidence: 75%
See 1 more Smart Citation
“…EMFs modulate the efficiency of cell death by altering the expression of calmodulin (CaM) and CaM-dependent proteins [42]. In summary, various in vitro and in vivo experimental studies highlighted here for their scientific quality [31][32][33][34][35][36][37][38][39][40][41][42] agree that the effect of ELF-MF (modulated or unmodulated) at the immune cell level depends on the oxidative status. Non-ionizing radiation in the 35-50 Hz frequency range and intensity of 1 to 7mT modulates antioxidant enzymes, increasing intracellular calcium levels, favouring therapy after cerebral vascular accidents, by modulating apoptosis caused by cytotoxic agents.…”
Section: Emf-induced Redox Stress May Modulate Apoptosis And/ or Necr...mentioning
confidence: 75%
“…However, the lack of cumulative effects with repeated exposure cannot be guaranteed. On exposure to an EMF of field strength 7mT, cellular adaptation is insufficient to prevent harmful effects [34].…”
Section: Emf-induced Redox Stress May Modulate Apoptosis And/ or Necr...mentioning
confidence: 99%
“…Several studies have shown that EMF exposure modifies physiological and biochemical processes leading to immune cell activation [ 15 ], resulting in increased reactive oxygen species (ROS) formation, enhanced phagocytic activity, and increased cytokine release [ 23 , 51 ]. It was shown that EMF can cause mild oxidative stress (increase in ROS and changes in antioxidant levels) in many tissues of the body [ 16 , 52 , 53 ]. The increase in plasma concentration of pro-inflammatory cytokines and an elevation in blood parameters, such as white blood cells, lymphocytes, hemoglobin, and hematocrit levels in rats exposed to EMF (50 Hz, 7 mT, 24 h) were also demonstrated [ 15 , 54 ].…”
Section: Electromagnetic Field and Neurodegenerative Diseasesmentioning
confidence: 99%
“…EMF treatment should be conducted under well-controlled conditions, supported by evidence of biological activity for EMF, which may lead to a positive or negative outcome depending on the exposure parameters. This is to ensure the safety of therapeutic treatments involving EMF, even more so when a direct action of an EMF occurring at one body location may have an indirect effect in another location [ 13 , 14 , 15 , 16 ]. According to published results, the most beneficial therapeutic cycle should include 10 to 14 daily treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation